2005
DOI: 10.1002/nme.1595
|View full text |Cite
|
Sign up to set email alerts
|

Efficient return algorithms for associated plasticity with multiple yield planes

Abstract: SUMMARYA new return method for implicit integration of linear isotropic yield criteria is presented. The basic idea is to perform all the manipulations in the principal stress space and thereby achieve very simple formulae for calculating the plastic corrector stresses, based on the constant gradient of such criteria. The return formulae are in closed form and no iteration is required. The method accounts for three types of stress return: return to a single yield plane, to a discontinuity line at the intersect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 19 publications
0
68
0
Order By: Relevance
“…This section provides that tangent following the approach of Clausen et al [2][3][4]. The tangent is first constructed in principal stress space and then transformed into six-component stress space using the eigenvectors associated with the trial elastic strain state (see Appendix B for details).…”
Section: Algorithmic Consistent Tangentmentioning
confidence: 99%
“…This section provides that tangent following the approach of Clausen et al [2][3][4]. The tangent is first constructed in principal stress space and then transformed into six-component stress space using the eigenvectors associated with the trial elastic strain state (see Appendix B for details).…”
Section: Algorithmic Consistent Tangentmentioning
confidence: 99%
“…As Clausen et al [4] have shown, the elasto-plastic consistent tangent for a hydrostatic apex return is simply given by…”
Section: Stress Origin Consistent Tangentmentioning
confidence: 99%
“…The consistent tangent for a corner return is obtained following the approach given by Clausen et al [4]. By considering the vector orientation of the edge…”
Section: Compression Meridian Consistent Tangentmentioning
confidence: 99%
See 2 more Smart Citations